(untitled) (Educational Perspectives Magazine (REPED), 2023)
Preschool education is the first level of education in our country, which aims to “promote a quality education and leaming relevant and permanent in children during their first years of life” to promote and achieve this goal today have been a number of educational proposals, which is the primary role played by the educator/ ra nursery. In our country, through the Foundations Curriculum for Preschool Education, provides a definition of the role played by the nursery teacher in their different functions, making it the main reference point for students and educators in service. It also recognizes the educational transition, as they provide múltiple axes energizing potential as lead groups of children who usually do not resort to them, considering them important because they are organized and there are important educational relations. Considering the new challenges and as an opportunity to provide top quality nursery education, the Metropolitan University of Educational Sciences at its headquarters in Santiago and Granary has implemented four years ago from Final Practice in new scenarios such as libraries, museums, and recently safari park in the sixth región, emerging as a complement and support the learning process of children from various schools, claiming also that these institutions come to be formally in a new educational setting that complements the educational process traditional, where children can learn about the libraries from another perspective, interacting and enjoying children’s literature as a first approach to reading and writing, as well as in the case of a museum, the cultural heritage their communities, cities or towns and the living beings represented in flora and fauna that live together in the parks. The following work experience and allows systematizes characterize and contextualize the roles played by a kindergarten teacher to intégrate these institutions and be part of a new team, where his contribution in the field of education has helped enrich the learning of children and youth.